RISK ASSESSMENT FOR PRODUCTION SEPARATOR IN SEPARATION SYSTEM BASED ON DNV RP-G101 CASE STUDY: LIMA FLOW STATION - MANURUNG (NIM : 13106023); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, IMMANUEL
Risk Assessment is an activity to calculate the value of the risk from a system and equipment. The purpose of risk assessment is to reduce and minimize the negative impacts that threaten the safety aspects, financial losses, nor environmental damage suffered by the company. This final project is to analyze the level and value of risk from a system (screening) and equipment (detailed assessment) using DNV RP-G101 that reviewing the Risk Assessment of Offshore Topside Static Mechanical Equipment. A case study performed on production separator of the platform LPRO separation system, Lima Flow Station. From the screening’s level, there’s systems that has a high level of risk and should be further analyzed at the level of detailed assessment on the system. It is include Wellhead, sand separator, separation, gas processing, gas compression, crude oil handling, drain system, fuel system, and flare system. By analyzing separation system in this final project there are three equipment with high risk value, including LPV-3 Top (Production Separator) with safety consequence value 3.925 (Category E), economic consequence value US$ 38693, and PoF 0.00118 (category 4 ); LPV-5 Top (LP Flare KO Drum) with a safety consequence value 1.8538 (Category E), economic consequence value US$ 38499, and PoF 0.00361 (category 4); LPV-7 Top (Fuel Gas Scrubber) with safety consequence value 2.13 (Category E), economic consequence value of US$ 166970, and PoF 0.00374 (category 4). With those high risk equipment level, there is so important to plan some further handling to reduce probability and consequence of failure, such as mitigation activity, repair the equipments, or replace the equipments for LPV-3, LPV-5, and LPV-7.